2019
DOI: 10.21037/jtd.2018.12.27
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter, sutureless and conventional aortic-valve replacement: a network meta-analysis of 16,432 patients

Abstract: Background: Minimally invasive surgical techniques pose alternatives to conventional surgery for the treatment of aortic stenosis (AS). We present a Bayesian network analysis comparing Valve Academic Research Consortium-2 clinical outcomes between transcatheter aortic valve implantation (TAVI), sutureless (SL-AVR) and conventional aortic valve replacement (CAVR). Methods: Electronic searches of databases were conducted and seven two-arm randomized-controlled trials and 25 propensity-score-matched studies compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 56 publications
(26 reference statements)
5
25
0
2
Order By: Relevance
“…Patient selection is a critical factor given the strengths and weaknesses of each approach. A recent meta-analysis (6) compared the three modalities and revealed no differences in 30-day mortality or postoperative stroke between them, but concluded that TAVR and SURD were associated with less postoperative bleeding. SURD was also associated with less acute renal injury, but more conduction disease compared to conventional AVR.…”
Section: Introductionmentioning
confidence: 99%
“…Patient selection is a critical factor given the strengths and weaknesses of each approach. A recent meta-analysis (6) compared the three modalities and revealed no differences in 30-day mortality or postoperative stroke between them, but concluded that TAVR and SURD were associated with less postoperative bleeding. SURD was also associated with less acute renal injury, but more conduction disease compared to conventional AVR.…”
Section: Introductionmentioning
confidence: 99%
“…When looking at short-term outcomes, there are many studies and meta-analyses that have tried to compare standard valves, sutureless valves and TAVI among patients with a range of surgical risk levels. Recently, a network meta-analysis of 16,432 patients from seven randomized controlled trials and twenty-five propensity score-matched studies have compared all three options (1). While mortality and stroke outcomes were comparable for all three options, the sutureless AVR demonstrated less regurgitation than TAVI and less major bleeding and acute kidney injury than conventional AVR (1).…”
Section: Introductionmentioning
confidence: 99%
“…18 Despite the euphoria of interventional cardiologists and TAVI experts, some drawbacks persist for this procedure including increased paravalvular regurgitation and pacemaker implantation rates, suboptimal TAVI deployment, or balloon inflation with the risk of annulus rupture, unknown long-term durability, and major vascular complications. 19,20 The above deficits of TAVI, in addition to the benefits of RAMT including the ability to remove the diseased valve leaflets, radically decalcify the annulus, and precisely size and implant the valve prosthesis under direct vision may make RAMT competitive with TAVI procedures. As a result of these benefits, we noted a low rate of paravalvular leak in the new pacemaker implantation (0.4% and 1.4%, respectively), significantly lower than those reported in the literature for TAVI.…”
Section: Discussionmentioning
confidence: 99%